Fatigue-resistant high-reliability solder paste and preparation method thereof

By using high-content alloy solder powder and modified paste flux, combined with electrospinning and high-temperature sintering technology, a fatigue-resistant and high-reliability solder paste was prepared, which solved the residual and fatigue problems after welding of traditional solder paste, and achieved the welding effect of high strength, low holes and high insulation impedance.

CN119589196AActive Publication Date: 2025-03-11SHENZHEN VITAL NEW MATERIAL CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411987095.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-11
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The residue of traditional oily solder paste is severe after welding, which affects the quality of the solder joint and can easily lead to fatigue failure of the solder joint, reduced strength and reduced insulation impedance, and increases the risk of leakage.

Method used

Fatigue-resistant and high-reliability solder paste made of 85-90% alloy solder powder and 10-15% paste flux, alloy solder powders include Sn, Ag, Cu, Sb, etc. Polyethylene glycol is used as paste to form a paste flux, and modified fillers are prepared through electrospinning and high-temperature sintering technology to form a fibrous mesh structure to improve insulation performance.

Benefits of technology

It achieves the effects of high welding strength, good fatigue resistance, low hollows and high insulation impedance, reducing the risk of post-weld residues and corrosion, and improving the reliability and safety of welding joints.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005222838770000061
    Figure BDA0005222838770000061
  • Figure BDA0005222838770000121
    Figure BDA0005222838770000121
  • Figure BDA0005222838770000131
    Figure BDA0005222838770000131
Patent Text Reader

Abstract

The invention relates to anti-fatigue high-reliability solder paste and a preparation method thereof. The solder paste is mainly prepared from the following raw materials in percentage by mass: 85-90% of alloy welding powder and 10-15% of paste flux, wherein the alloy welding powder comprises main body welding powder, alloy powder A and alloy powder B; the paste flux comprises the following raw materials in parts by weight: 5-10 parts of an activating agent, 1-5 parts of a rheological agent, 20-30 parts of an organic solvent, 20-30 parts of a paste forming agent, 0.1-0.5 part of a modified filler and 0.1-0.5 part of a corrosion inhibitor. The solder paste has the advantages of being good in welding strength, resistant to fatigue, low in cavity and high in insulation resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of solder paste, and in particular to a fatigue-resistant and highly reliable solder paste and a preparation method thereof. Background Art

[0002] Traditional solder paste is generally oily solder paste. Due to the large amount of rosin and resin used as flux components, the residue after welding becomes viscous and difficult to be completely removed by conventional cleaning methods. The residue after welding is relatively serious and causes corrosion to the base plate. The grease components in oily solder paste will affect the formation quality of solder joints, such as producing defects such as bubbles and voids. These defects will aggravate the fatigue failure of solder joints and reduce the strength of solder joints, making them more prone to breakage or deformation when subjected to external forces, thereby reducing the fatigue resistance of solder joints. Grease and other non-polar contaminants in oily solder paste may cover solder joints or circuit boards to form a conductive film, resulting in reduced insulation resistance. The reduction in insulation impedance will increase the risk of leakage, especially under high humidity or high voltage conditions, where leakage may be more serious, posing a threat to the performance and safety of circuit boards. Summary of the invention

[0003] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a fatigue-resistant and highly reliable solder paste having the advantages of good welding strength, fatigue resistance, low voids and high insulation resistance and a preparation method thereof.

[0004] To achieve the above object, the technical solution adopted by the present invention is:

[0005] In a first aspect, the present invention provides a fatigue-resistant and highly reliable solder paste, which is made of the following raw materials in percentage by mass: 85-90% of alloy solder powder and 10-15% of paste flux, wherein the alloy solder powder includes main solder powder, alloy powder A and alloy powder B, the main solder powder includes Sn, Ag, Cu and Sb, the alloy powder A includes Bi and / or In, and the alloy powder B includes at least one of Co, Ni, Ti, Nb, Cr, Mo and B;

[0006] The paste flux comprises the following raw materials in parts by weight: 5-10 parts of an activator, 1-5 parts of a rheological agent, 20-30 parts of an organic solvent, 20-30 parts of a paste-forming agent, 0.1-0.5 parts of a modified filler and 0.1-0.5 parts of a corrosion inhibitor;

[0007] The activator is succinic acid and adipic acid in a mass ratio of 1:(1.5-3), the rheological agent is a polyamide rheological agent, the organic solvent is a composition of a low boiling point solvent and a high boiling point solvent in a mass ratio of (1-2):1, the low boiling point solvent includes dipropylene glycol methyl ether and / or ethylene glycol monobutyl ether, the high boiling point solvent includes at least one of tripropylene glycol butyl ether, diethylene glycol butyl ether, hexanediol, 2-ethyl-1,3 hexanediol and pentanediol, and the paste-forming agent is polyethylene glycol;

[0008] The preparation method of the modified filler comprises the following steps:

[0009] S1. Mix nickel powder, aluminum oxide and a co-solvent, stir evenly, and obtain a precursor dispersion liquid, wherein the co-solvent is a mixed solvent of ethanol, hydrochloric acid and acetic acid, and the mass ratio of the co-solvent, the nickel powder and the aluminum oxide is (5-6):1:(1.5-3);

[0010] S2, adding polyvinyl pyrrolidone to the precursor dispersion, stirring evenly, to obtain a precursor dispersion, wherein the mass ratio of polyvinyl pyrrolidone to the precursor dispersion is (0.1-0.2):1;

[0011] S3, electrospinning the precursor dispersion to obtain composite fiber paper, drying it, and sintering it in an oxygen-free environment at 1000-1500° C.;

[0012] S4. Soak the sintered composite fiber paper in an epoxy resin mixture for curing, take it out and crush it to obtain a modified filler, wherein the epoxy resin mixture includes a mixture of epoxy resin, curing agent and catalyst in a mass ratio of 1:1:(0.01-0.03); the mass ratio of epoxy resin to sintered composite fiber paper is (2-3):1.

[0013] The solder paste of the present invention does not add a large amount of rosin and resin components as flux components, but uses polyethylene glycol as a paste-forming agent, which has the advantages of less residue after welding, less corrosion to the substrate, and no need for cleaning. The modified filler of the present invention is first prepared by electrostatic spinning technology and high-temperature sintering technology to obtain a composite fiber paper of aluminum oxide and nickel, and then impregnated in epoxy resin for curing, thereby obtaining the modified filler. The modified filler has a fibrous grid structure, that is, a flexible, bendable and independent grid is formed, which is characterized in that there are nano-scale gaps between single fiber grids, so the air between the grid gaps can effectively prevent the flow of electrons, thereby improving the insulation performance of the material. In contrast, directly mixing aluminum oxide, nickel powder and epoxy resin will increase the electronic conduction path due to more contact between the filler and the matrix, thereby reducing the insulation performance.

[0014] The addition of alumina and nickel can improve the mechanical strength and toughness of solder paste, thereby improving the fatigue resistance of solder joints. When alumina and nickel are made into fiber paper, because of its continuous network structure, it can provide better stress distribution and additional mechanical support, making the solder joints more solid, thereby improving the fatigue resistance of solder paste solder joints. This structure can effectively disperse periodic stress and reduce the generation and expansion of fatigue cracks. Alumina is an excellent electrical insulating material, and its addition can significantly improve the insulation resistance of solder paste. Epoxy resin itself has good insulation properties, which can improve the insulation resistance of solder paste and reduce the risk of leakage and short circuit when electronic devices are working. However, the addition of nickel improves the fluidity and wettability of solder paste, which helps the solder paste to better fill the pad during printing and reflow and reduce the formation of voids. However, since nickel is a conductive material, it will reduce the insulation resistance. When the mass ratio of co-solvent, nickel powder and alumina is in the range of (5-6):1:(1.5-3), the insulation resistance and wettability of solder paste meet the requirements.

[0015] The activator is a composition of succinic acid and adipic acid, and the active temperatures of the two are different. Succinic acid is active at 180-230°C, and it will decompose when it exceeds 230°C, so there is no residue after welding, while adipic acid is active at 230-260°C, just in the welding area, which can effectively reduce welding voids. In order to improve the compatibility between the components of the solder paste, the present invention selects a composition to which a low-boiling point solvent and a high-boiling point solvent are added. The boiling point of the low-boiling point solvent is between 150-200°C, and the boiling point of the high-boiling point solvent is between 210-260°C. The low-boiling point organic solvent will evaporate rapidly during the welding process, which can reduce the risk of the solder paste collapsing after printing, thereby improving the printing accuracy, and at the same time help to reduce the viscosity of the solder paste during printing and welding, and improve printability. Moreover, the rapid volatilization of the low-boiling point solvent will cause the solder paste to increase its fluidity during the welding process, which helps to spread the solder on the pad and improve the welding performance. High-boiling-point organic solvents evaporate more slowly during the soldering process and are more stable at high temperatures, which helps maintain the performance of solder paste during the soldering process and affects the printability and collapse of solder paste. The addition of low-boiling-point solvents in organic solvents is greater than that of high-boiling-point solvents, which can avoid leaving more residues, thereby improving the insulation performance and reliability of solder joints.

[0016] It should be noted that the paste flux of the present invention is suitable for soldering lead-free main body solder powder at 180-260°C.

[0017] More preferably, the alloy solder powder consists of the following components, measured by mass percentage: Ag 0.1-5.0%, Cu 0.1-1.0%, Sb 1-6%, In 1-5%, Bi 1-5%, Co 0.005-0.1%, Ni 0.05-0.1%, Ti 0.001-0.5%, Nb 0.001-0.3%, Cr 0.005-0.1%, Mo 0.005-0.2%, B 0.001-0.01%, and the balance is Sn and unavoidable impurities.

[0018] Preferably, the corrosion inhibitor is triazole and / or benzotriazole.

[0019] More preferably, in the step S1 of modifying the filler, the mass ratio of the co-solvent, the nickel powder and the aluminum oxide is 5:1:(2-2.5).

[0020] Preferably, the low boiling point solvent is a composition of dipropylene glycol methyl ether and ethylene glycol monobutyl ether in a mass ratio of 1: (0.5-0.7), and the high boiling point solvent is a composition of tripropylene glycol butyl ether and diethylene glycol butyl ether in a mass ratio of 1: (0.8-1).

[0021] Preferably, the weight average molecular weight of the polyethylene glycol is 2000-6000.

[0022] Preferably, the volume ratio of ethanol, hydrochloric acid and acetic acid in the co-solvent is (9-11):1:1.

[0023] Preferably, the curing agent is hexahydrophthalic anhydride; and the catalyst is imidazole.

[0024] Preferably, in the preparation step S3 of the modified filler, the drying temperature is 70-80° C., the drying time is 10-14 h, and the sintering time is 1-2 h.

[0025] Preferably, in the preparation step S4 of the modified filler, the curing is a three-stage curing, and the temperature of the first stage curing is 65-75°C and the time is 1-2h. The low-temperature curing at this stage helps the initial cross-linking of the epoxy resin to form a certain intermolecular connection, but it will not be completely cured. At this stage, the resin begins to cure, but the degree of curing is low, which helps to reduce the thermal stress and volume shrinkage inside the material and avoid cracking or deformation caused by rapid curing. Low-temperature curing helps the epoxy resin to better infiltrate the composite fiber paper and enhance the interface bonding.

[0026] The second stage of curing is at a temperature of 100-120°C and a time of 1-2 hours. At this stage, the higher temperature can accelerate the cross-linking reaction of the epoxy resin and further improve the degree of curing. As the degree of curing increases, the mechanical properties of the modified filler, such as strength and toughness, are enhanced, and the internal stress caused by volume shrinkage during the curing process can be further reduced.

[0027] The third stage of curing is at 140-160°C for 3-4 hours. The high temperature at this stage ensures that the epoxy resin is fully cured and forms a stable three-dimensional network structure. Fully cured epoxy resin can provide optimal physical and chemical properties, such as high strength, high modulus and good heat resistance. Long-term high-temperature curing helps ensure the long-term stability and reliability of the modified filler, especially in applications under high temperature environments.

[0028] In a second aspect, the present invention provides a method for preparing a fatigue-resistant and highly reliable solder paste, comprising the following steps:

[0029] (1) heating and stirring an activator, a rheological agent, an organic solvent, a paste-forming agent and a corrosion inhibitor until they are uniformly mixed, then heating the mixture to 70-80° C., adding a modified filler, and stirring the mixture to obtain the paste flux;

[0030] (2) After the temperature of the paste flux drops to 25±3° C., gradually add alloy solder powder to the paste flux and stir evenly to obtain the fatigue-resistant and highly reliable solder paste.

[0031] Preferably, in step (1), the heating temperature is 50-60° C., the stirring speed is 200-300 rpm, and the time is 10-30 min. After adding the modified filler, the stirring speed is 500-600 rpm, and the time is 1-2 h.

[0032] Preferably, in step (2), the stirring temperature is 25±3° C., the stirring speed is 30-60 rpm, and the time is 20-30 min.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] The solder paste of the present invention has the advantages of good welding strength, fatigue resistance, low voids and high insulation resistance. Because the solder paste does not contain a large amount of rosin and resin components as flux components, but uses polyethylene glycol as a paste-forming agent, it has the advantages of less residue after welding, less corrosion to the substrate, and no need for cleaning. The modified filler is a composite fiber paper impregnated in epoxy resin and solidified. The composite fiber paper has a fibrous grid structure, and the air between the grid gaps can effectively prevent the flow of electrons, thereby improving the insulation performance of the material; the addition of aluminum oxide and nickel can improve the mechanical strength and toughness of the solder paste, thereby improving the fatigue resistance of the welding point; aluminum oxide and epoxy resin can improve the insulation resistance of the solder paste; the addition of nickel improves the fluidity and wettability of the solder paste, which helps the solder paste to better fill the pad during printing and reflow, and reduce the formation of voids. The activator uses a combination of succinic acid and adipic acid, and the active temperatures of the two are different. They can be active in the range of 180-260°C, thereby reducing the residue and void rate. The organic solvent is a combination of a low-boiling point solvent and a high-boiling point solvent. The low-boiling point organic solvent evaporates quickly during the welding process, which can reduce the risk of solder paste collapse after printing, thereby improving printing accuracy, and at the same time helps to reduce the viscosity of the solder paste during printing and welding and improve printability; the high-boiling point organic solvent evaporates slowly during the welding process and is more stable at high temperatures, which helps to maintain the performance of the solder paste during the welding process. DETAILED DESCRIPTION

[0035] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.

[0036] The sources of reagents used in the following examples and comparative examples are as follows:

[0037] Polyamide rheological agent: the manufacturer is CRAY VALLEY, France, the brand is CRAY VALLEY Super;

[0038] Epoxy resin: The manufacturer is Dow Chemical Company, the brand is DER6510HT;

[0039] Hexahydrophthalic anhydride: The manufacturer is Shanghai MacLean Biochemical Technology Co., Ltd., brand number C804848;

[0040] Imidazole: manufacturer is Shanghai Aladdin Biochemical Technology Co., Ltd., brand number 432539;

[0041] Polyethylene glycol: polyethylene glycol 2000, polyethylene glycol 4000, and polyethylene glycol 6000 were purchased from Dow Chemical Co.;

[0042] Triazole: The manufacturer is Guangdong Wengjiang Chemical Reagent Co., Ltd., the brand is PB08294;

[0043] Benzotriazole: The manufacturer is Guangdong Wengjiang Chemical Reagent Co., Ltd., brand name PA01680;

[0044] Polyvinylpyrrolidone: The manufacturer is Guangdong Wengjiang Chemical Reagent Co., Ltd., and the brand number is PA039018.

[0045] The purity of the metal materials used in the embodiments and comparative examples is greater than 99.9%.

[0046] Other materials and reagents, unless otherwise specified, can be obtained from commercial sources.

[0047] Examples 1-9 and Comparative Examples 1-16

[0048] The alloy solder powder used in the solder paste of each embodiment and comparative example includes a main solder powder, an alloy powder A and an alloy powder B, wherein the main solder powder includes Sn, Ag, Cu and Sb, the alloy powder A includes Bi and In, and the alloy powder B includes Co, Ni, Ti, Nb, Cr, Mo and B. Specifically, the alloy solder powder is composed of the following components by mass percentage:

[0049]

[0050] The balance is Sn and inevitable impurities.

[0051] Example 1

[0052] A fatigue-resistant and highly reliable solder paste, which is made of the following raw materials in percentage by mass: 88.5% of alloy solder powder and 11.5% of paste flux; wherein the paste flux comprises the following raw materials in parts by weight: 8 parts of activator, 3 parts of rheological agent, 23 parts of organic solvent, 25 parts of paste forming agent, 0.3 parts of modified filler and 0.4 parts of corrosion inhibitor;

[0053] The activator is succinic acid and adipic acid in a mass ratio of 1:2; the rheological agent is a polyamide rheological agent; the organic solvent is a composition of a low boiling point solvent and a high boiling point solvent in a mass ratio of 1.5:1, the low boiling point solvent is a composition of dipropylene glycol methyl ether and ethylene glycol monobutyl ether in a mass ratio of 1:0.7, and the high boiling point solvent is a composition of tripropylene glycol butyl ether and diethylene glycol butyl ether in a mass ratio of 1:1; the paste-forming agent is polyethylene glycol 4000; and the corrosion inhibitor is benzotriazole;

[0054] The preparation method of the modified filler comprises the following steps:

[0055] S1. Mix nickel powder, aluminum oxide and a co-solvent, stir evenly, and obtain a precursor dispersion, wherein the co-solvent is a mixed solvent of ethanol, hydrochloric acid and acetic acid in a volume ratio of 10:1:1, and the mass ratio of the co-solvent, nickel powder and aluminum oxide is 5:1:2.5;

[0056] S2, adding polyvinyl pyrrolidone to the precursor dispersion, stirring evenly, to obtain a precursor dispersion, wherein the mass ratio of polyvinyl pyrrolidone to the precursor dispersion is 0.15:1;

[0057] S3. Electrospin the precursor dispersion to obtain composite fiber paper, dry it at 75°C for 12 h, and sinter it at 1200°C in an oxygen-free environment for 1.5 h. The electrospinning parameters are as follows: positive voltage 10 kV, negative voltage 2 kV, fixed infusion speed 0.05 mm·min -1 , rotating collector speed 100r·min -1 ;

[0058] S4. Soak the sintered composite fiber paper in an epoxy resin mixture for curing, take it out and crush it to obtain the modified filler, wherein the epoxy resin mixture is a mixture of epoxy resin, curing agent and catalyst in a mass ratio of 1:1:0.02, the curing agent is hexahydrophthalic anhydride, the catalyst is imidazole, and the mass ratio of epoxy resin to sintered composite fiber paper is 2.5:1; the curing is a three-stage curing, the first stage curing temperature is 70°C, the time is 2h, the second stage curing temperature is 110°C, the time is 1h, and the third stage curing temperature is 150°C, the time is 3h.

[0059] The method for preparing fatigue-resistant and highly reliable solder paste comprises the following steps:

[0060] (1) heating an activator, a rheological agent, an organic solvent, a paste-forming agent and a corrosion inhibitor at 55° C. and stirring at a speed of 250 rpm for 20 min, heating to 75° C. and adding a modified filler, stirring at 550 rpm for 1.5 h, cooling, and grinding to obtain the paste flux;

[0061] (2) gradually adding alloy solder powder into the paste flux, stirring at a rotation speed of 40 rpm for 25 minutes, to obtain the fatigue-resistant and high-reliability solder paste.

[0062] Example 2

[0063] A fatigue-resistant and highly reliable solder paste, which is made of the following raw materials in percentage by weight: 85% alloy solder powder and 15% paste flux; wherein the paste flux comprises the following raw materials in parts by weight: 5 parts of activator, 1 part of rheological agent, 20 parts of organic solvent, 20 parts of paste forming agent, 0.1 parts of modified filler and 0.1 parts of corrosion inhibitor;

[0064] The activator is succinic acid and adipic acid in a mass ratio of 1:1.5, and the rheological agent is a polyamide rheological agent; the organic solvent is a composition of a low boiling point solvent and a high boiling point solvent in a mass ratio of 1:1, the low boiling point solvent is a composition of dipropylene glycol methyl ether and ethylene glycol monobutyl ether in a mass ratio of 1:0.5, and the high boiling point solvent is a composition of tripropylene glycol butyl ether and diethylene glycol butyl ether in a mass ratio of 1:0.8; the paste-forming agent is polyethylene glycol 2000, and the corrosion inhibitor is triazole;

[0065] The preparation method of the modified filler comprises the following steps:

[0066] S1. Mix nickel powder, aluminum oxide and a co-solvent, stir evenly, and obtain a precursor dispersion; wherein the co-solvent is a mixed solvent of ethanol, hydrochloric acid and acetic acid in a volume ratio of 9:1:1, and the mass ratio of the co-solvent, nickel powder and aluminum oxide is 5:1:1.5;

[0067] S2, adding polyvinyl pyrrolidone to the precursor dispersion, stirring evenly, to obtain a precursor dispersion; wherein the mass ratio of polyvinyl pyrrolidone to the precursor dispersion is 0.1:1;

[0068] S3. Electrospin the precursor dispersion to obtain composite fiber paper, dry it at 70°C for 14 h, and sinter it at 1000°C for 2 h in an oxygen-free environment. The electrospinning parameters are as follows: positive voltage 10 kV, negative voltage 2 kV, fixed infusion speed 0.05 mm·min -1 , rotating collector speed 100r·min -1 .

[0069] S4. Soak the sintered composite fiber paper in an epoxy resin mixture for curing, take it out and crush it to obtain a modified filler, wherein the epoxy resin mixture includes a mixture of epoxy resin, a curing agent and a catalyst in a mass ratio of 1:1:0.01, the curing agent is hexahydrophthalic anhydride, the catalyst is imidazole, and the mass ratio of epoxy resin to composite fiber paper is 2:1; the curing is a three-stage curing, the first stage curing temperature is 65°C, the time is 2h, the second stage curing temperature is 100°C, the time is 2h, and the third stage curing temperature is 140°C, the time is 3h.

[0070] The method for preparing fatigue-resistant and highly reliable solder paste comprises the following steps:

[0071] (1) heating an activator, a rheological agent, an organic solvent, a paste-forming agent and a corrosion inhibitor at 50° C. and stirring at a speed of 200 rpm for 30 min, heating to 70° C. and adding a modified filler, stirring at 500 rpm for 1 h, cooling, and grinding to obtain the paste flux;

[0072] (2) gradually adding alloy solder powder into the paste flux, stirring at a rotation speed of 30 rpm for 30 minutes, to obtain the fatigue-resistant and high-reliability solder paste.

[0073] Example 3

[0074] A fatigue-resistant and highly reliable solder paste, which is made of the following raw materials in percentage by mass: 90% alloy solder powder and 10% paste flux; wherein the paste flux comprises the following raw materials in parts by weight: 10 parts of activator, 5 parts of rheological agent, 30 parts of organic solvent, 30 parts of paste forming agent, 0.5 parts of modified filler and 0.5 parts of corrosion inhibitor;

[0075] The activator is succinic acid and adipic acid in a mass ratio of 1:3, and the rheological agent is a polyamide rheological agent; the organic solvent is a composition of a low boiling point solvent and a high boiling point solvent in a mass ratio of 2:1, the low boiling point solvent is dipropylene glycol methyl ether, and the high boiling point solvent is a composition of hexanediol, 2-ethyl-1,3 hexanediol and pentanediol in a mass ratio of 1:1:1; the paste-forming agent is polyethylene glycol 6000, and the corrosion inhibitor is a composition of triazole and benzotriazole in a mass ratio of 1:1;

[0076] The preparation method of the modified filler comprises the following steps:

[0077] S1. Mix nickel powder, aluminum oxide and a co-solvent, stir evenly, and obtain a precursor dispersion; wherein the co-solvent is a mixed solvent of ethanol, hydrochloric acid and acetic acid in a volume ratio of 11:1:1, and the mass ratio of the co-solvent, nickel powder and aluminum oxide is 6:1:3;

[0078] S2, adding polyvinyl pyrrolidone to the precursor dispersion, stirring evenly, to obtain a precursor dispersion; wherein the mass ratio of polyvinyl pyrrolidone to the precursor dispersion is 0.2:1;

[0079] S3. Electrospin the precursor dispersion to obtain composite fiber paper, dry it at 80°C for 10 h, and sinter it at 1500°C for 1 h in an oxygen-free environment. The electrospinning parameters are as follows: positive voltage 10 kV, negative voltage 2 kV, fixed infusion speed 0.05 mm·min -1 , rotating collector speed 100r·min -1 ;

[0080] S4, soak the sintered composite fiber paper in epoxy resin mixture for curing, take it out and crush it to obtain modified filler, wherein the epoxy resin mixture includes a mixture of epoxy resin, curing agent and catalyst in a mass ratio of 1:1:0.03, the curing agent is hexahydrophthalic anhydride, and the catalyst is imidazole. The mass ratio of epoxy resin to composite fiber paper is 3:1; the curing is a three-stage curing, the first stage curing temperature is 75°C, the time is 1h, the second stage curing temperature is 120°C, the time is 1h, and the third stage curing temperature is 160°C, the time is 3h.

[0081] The method for preparing fatigue-resistant and highly reliable solder paste comprises the following steps:

[0082] (1) heating an activator, a rheological agent, an organic solvent, a paste-forming agent and a corrosion inhibitor at 60° C. and stirring at a speed of 300 rpm for 30 min, heating to 80° C. and adding a modified filler, stirring at a speed of 600 rpm for 1 h, cooling, and grinding to obtain the paste flux;

[0083] (2) gradually adding alloy solder powder into the paste flux and stirring at 50 rpm for 20 min to obtain the fatigue-resistant and high-reliability solder paste.

[0084] Example 4

[0085] The difference between Example 4 and Example 1 is that the mass ratio of nickel powder to aluminum oxide in the modified filler is 1:1.5.

[0086] Example 5

[0087] The difference between Example 5 and Example 1 is that the mass ratio of nickel powder to aluminum oxide in the modified filler is 1:2.

[0088] Example 6

[0089] The difference between Example 6 and Example 1 is that the mass ratio of nickel powder to aluminum oxide in the modified filler is 1:3.

[0090] Example 7

[0091] The difference between Example 7 and Example 1 is that the total amount of organic solvent and the mass ratio of high boiling point solvent to low boiling point solvent are kept unchanged, the low boiling point solvent is dipropylene glycol methyl ether; and the high boiling point solvent is a composition of tripropylene glycol butyl ether and diethylene glycol butyl ether in a mass ratio of 1:1.

[0092] Example 8

[0093] The difference between Example 8 and Example 1 is that the total amount of organic solvent and the mass ratio of high boiling point solvent to low boiling point solvent are kept unchanged, the low boiling point solvent is a composition of dipropylene glycol methyl ether and ethylene glycol monobutyl ether in a mass ratio of 1:0.7; the high boiling point solvent is tripropylene glycol butyl ether in a mass ratio of 1:0.7.

[0094] Example 9

[0095] The difference between Example 9 and Example 1 is that the total amount of the organic solvent and the mass ratio of the high boiling point solvent to the low boiling point solvent are kept unchanged, the low boiling point solvent is dipropylene glycol methyl ether; and the high boiling point solvent is tripropylene glycol butyl ether.

[0096] Comparative Example 1

[0097] The difference between Comparative Example 1 and Example 1 is that the modified filler is not added.

[0098] Comparative Example 2

[0099] The difference between Comparative Example 2 and Example 1 is that no alumina is added to the modified filler, and the missing alumina is supplemented with an equal amount of nickel powder.

[0100] Comparative Example 3

[0101] The difference between Comparative Example 3 and Example 1 is that no nickel powder is added to the modified filler, and the missing nickel powder is supplemented with an equal amount of alumina.

[0102] Comparative Example 4

[0103] The difference between Comparative Example 4 and Example 1 is that in the step S3 of preparing the modified filler, the composite fiber paper is not sintered after being obtained.

[0104] Comparative Example 5

[0105] The difference between Comparative Example 5 and Example 1 is that the preparation step S4 of the modified filler is to directly grind the sintered composite fiber paper to obtain the modified filler.

[0106] Comparative Example 6

[0107] The difference between Comparative Example 6 and Example 1 is that the preparation method of the modified filler does not include steps S2-S4, but directly adds the precursor dispersion into the epoxy resin mixed liquid, stirs evenly, vacuum-suctions the mixture, and dries it to obtain the modified filler, wherein the composition and addition amount of the epoxy resin mixed liquid are the same as those in Example 1.

[0108] Comparative Example 7

[0109] The difference between Comparative Example 7 and Example 1 is that the total amount of nickel powder and aluminum oxide remains unchanged, and the mass ratio of nickel powder to aluminum oxide in the modified filler is 1:1.

[0110] Comparative Example 8

[0111] The difference between Comparative Example 8 and Example 1 is that the total amount of nickel powder and aluminum oxide remains unchanged, and the mass ratio of nickel powder to aluminum oxide in the modified filler is 1:3.5.

[0112] Comparative Example 9

[0113] The difference between Comparative Example 9 and Example 1 is that the total amount of the activator remains unchanged, and only succinic acid is added.

[0114] Comparative Example 10

[0115] The difference between Comparative Example 10 and Example 1 is that the total amount of the activator remains unchanged, and only adipic acid is added.

[0116] Comparative Example 11

[0117] The difference between Comparative Example 11 and Example 1 is that the total amount of the activator remains unchanged, which is succinic acid and adipic acid in a mass ratio of 1:1.

[0118] Comparative Example 12

[0119] The difference between Comparative Example 12 and Example 1 is that the total amount of the activator remains unchanged, which is succinic acid and adipic acid in a mass ratio of 1:3.5.

[0120] Comparative Example 13

[0121] The difference between Comparative Example 13 and Example 1 is that the total amount of the organic solvent remains unchanged, and only the low boiling point solvent is added.

[0122] Comparative Example 14

[0123] The difference between Comparative Example 14 and Example 1 is that the total amount of the organic solvent remains unchanged, and only the high boiling point solvent is added.

[0124] Comparative Example 15

[0125] The difference between Comparative Example 15 and Example 1 is that the total amount of the organic solvent remains unchanged, which is a composition of a low boiling point solvent and a high boiling point solvent in a mass ratio of 0.5:1.

[0126] Comparative Example 16

[0127] The difference between Comparative Example 16 and Example 1 is that the total amount of the organic solvent remains unchanged, which is a composition of a low boiling point solvent and a high boiling point solvent in a mass ratio of 2.5:1.

[0128] Performance Testing

[0129] 1. Surface insulation resistance: The surface resistance of the solder pastes of Examples 1-9 and Comparative Examples 1-16 was tested with an insulation resistance tester. The specific data are shown in Table 1.

[0130] 2. Void rate: The void rates of solder joints formed by welding with alloy solder powder and paste flux in each group were measured by section microscopic observation method. The specific data are shown in Table 1.

[0131] 3. Expansion rate: Select a standard copper sheet, and use it as a test piece after polishing, pickling, baking and other process treatments; the solder wire is prepared from the alloy solder powder in each embodiment and comparative example, the wire diameter of the solder wire is 1.5-1.6mm, and it is wound into a ring with an inner diameter of 3mm. The welding test temperature is 240℃. During the test, place the prepared solder ring in the center of the standard copper sheet, and then apply about 10% paste flux into the ring; then place the test piece on the surface of the tin melting furnace set at the welding temperature, take it out after 20 seconds, and measure the solder joint height (h) after cooling and cleaning the residue with solvent.

[0132] The calculation of expansion rate (S) is as follows: SR = (D-h) / D × 100%

[0133] Where D is the diameter of the solder ball that is assumed to have the same volume as the solder ring used, that is, D = 1.24V1 / 3,

[0134] V=m / ρ, where m is the mass of the solder ring (obtained by weighing) and ρ is the density of the solder ring.

[0135] 4. Residue: The test base material is a copper substrate of 30mm×30mm×0.1mm. The solder paste of each group is coated on the base material in equal amounts and soldered at 240℃ for 2s. The residue content after soldering is calculated by the mass change before and after soldering. Each solder paste is soldered at least 5 times with a weighing accuracy of ±0.001g. The residue content after soldering Δm is calculated using formula (1) and the average value is taken as follows: Δm=1000×[0.17m1-(m2-m3)], (1);

[0136] Formula (1): m1 is the printing mass of solder paste on the copper substrate, g; m2 is the total mass of solder paste and copper substrate before soldering, g; m3 is the total mass of solder paste and copper substrate after soldering, g.

[0137] 5. Fatigue resistance: First, print the solder paste of each group on the PCB board, and then perform reflow soldering. Test the bonding strength of the solder joints. Then send the samples of each group into a small rapid temperature change test chamber for thermal cycle testing. The thermal cycle cycle is 1000 times. The cycle unit is: heating from -40℃ to 125℃ for 15min, keeping at 125℃ for 30min, cooling from 125℃ to -40℃ for 15min, keeping at -40℃ for 30min, and then test the bonding strength of the solder joints after taking them out. The test method of bonding strength is: test the shear strength of the fracture of each group of solder joints.

[0138] Table 1 Test results of each group of samples

[0139]

[0140]

[0141] It can be seen from Table 1 that since no rosin is added to the solder pastes of each group and the amount of epoxy resin added is relatively low, the residual amount of solder paste of each group after welding does not exceed 10 mg.

[0142] Example 1 and Comparative Examples 1 to 3 explore the effect of the modified filler on the performance of solder paste. Compared with Example 1, Comparative Example 1 does not add the modified filler, and its insulation resistance, fatigue resistance and wettability are significantly reduced; while in Comparative Example 2, no alumina is added, and its insulation resistance and fatigue resistance are significantly reduced, indicating that alumina can improve the mechanical strength and toughness of the solder paste, thereby improving the fatigue resistance of the solder joint, and at the same time, as an electrical insulating material, its addition can significantly improve the insulation resistance of the solder paste; in Comparative Example 3, no nickel powder is added, although the insulation resistance is slightly higher than that of Example 1, the fatigue resistance and wettability of the solder paste are significantly reduced, indicating that the combined application of alumina and nickel can make the solder paste have good insulation resistance, fatigue resistance and wettability.

[0143] Example 1, Examples 4 to 6 and Comparative Examples 7 to 8 explored the effect of the mass ratio of nickel powder and alumina in the modified filler on the performance of the solder paste. From the results in Table 1, it can be seen that the addition of alumina and nickel can improve the mechanical properties and fatigue resistance of the solder paste, but alumina is an insulating material and can significantly improve the insulation resistance performance of the solder paste, while nickel, as a conductive material, will reduce the insulation resistance. When the mass ratio of co-solvent, nickel powder and alumina is in the range of 5:1:(1.5-3), the insulation resistance and wetting performance of the solder paste meet the requirements, and more preferably 5:1:(2 to 2.5).

[0144] Example 1 and Comparative Examples 13-14 explore the influence of the selection of low boiling point solvents and high boiling point solvents in organic solvents on the performance of solder paste. Compared with Example 1, the total amount of organic solvents in Comparative Example 13 remains unchanged, and only low boiling point solvents are added. However, since the low boiling point solvent will decompose first during the high temperature welding process, the stability of the solder paste is reduced during the high temperature process, thereby significantly reducing the insulation resistance and fatigue resistance; Comparative Example 14 only adds high boiling point solvents, and its wettability is significantly reduced. This is because the rapid volatilization of low boiling point solvents will increase the fluidity of the solder paste during the welding process, which helps to spread the solder on the pad and improve the welding performance. Therefore, the present invention selects low boiling point solvents and high boiling point solvents as organic solvents, which can improve the compatibility between the components of the solder paste, because the boiling point of the low boiling point solvent is between 150-200°C, and the boiling point of the high boiling point solvent is between 210-260°C, which can be compounded with activators with different boiling points to maintain the performance of the solder paste during the welding process of 150-230°C.

[0145] Example 1, Examples 7 to 9 and Comparative Examples 15 to 16 explore the effect of the selection of the dosage ratio of low-boiling point solvents and high-boiling point solvents in organic solvents on the performance of solder pastes. It can be seen from the results in Table 1 that when the low-boiling point solvent is a composition of dipropylene glycol methyl ether and ethylene glycol monobutyl ether in a mass ratio of 1:0.7, and the high-boiling point solvent is a composition of tripropylene glycol butyl ether and diethylene glycol butyl ether in a mass ratio of 1:1, the performance of the solder paste can reach the best; while the organic solvents in Comparative Examples 15 and 16 are respectively excessive and too low in the amount of low-boiling point solvent added, and the performance of the solder paste is reduced. Therefore, the present invention limits the organic solvent to a composition of a low-boiling point solvent and a high-boiling point solvent in a mass ratio of (1-2):1, that is, the amount of low-boiling point solvent added in the organic solvent is slightly more than the high-boiling point solvent, which can avoid leaving more residues, thereby improving the insulation performance and reliability of the welding point.

[0146] Comparative Examples 4 to 6 explored the effect of the preparation method of the modified filler on the performance of the solder paste. In the preparation method of the modified filler in Comparative Example 4, the composite fiber paper was obtained without sintering, and the performance of the solder paste was significantly reduced. This is because high-temperature sintering can promote the mutual fusion of alumina and nickel with the fibers to improve the interfacial bonding between alumina and nickel fibers and enhance their mechanical strength and stability. The high temperature during the sintering process allows the fiber grains to grow and connect to each other, thereby improving the overall strength of the material. Moreover, sintering can make the composite fibers form a denser structure and reduce the porosity, thereby improving the overall performance of the material, including mechanical properties and thermal conductivity.

[0147] No epoxy resin is added to the modified filler of Comparative Example 5, and the various properties of the solder paste are significantly reduced. Epoxy resin is an excellent insulating material with high resistivity and good electrical insulation properties. Moreover, the epoxy resin wraps the nickel powder, which can improve the dispersibility of the modified filler and prevent the nickel powder from forming a conductive path to improve the insulation resistance of the solder paste. Moreover, the epoxy resin can reduce the surface tension, making it easier for the solder paste to spread on the pad.

[0148] The modified filler of Comparative Example 6 does not undergo the electrospinning step and the sintering step, and the various properties of the solder paste are significantly reduced. Because electrospinning and sintering can make the composite of aluminum oxide and nickel have a fibrous structure, the internal gaps and the air between the fibers can effectively prevent the flow of electrons, thereby improving the insulation performance of the material. At the same time, because it has a continuous network structure, it can provide better stress distribution and additional mechanical support, making the soldering point more solid, thereby improving the fatigue resistance of the solder paste soldering point. In contrast, directly mixing aluminum oxide, nickel powder and epoxy resin will increase the electronic conduction path due to more contact between the filler and the matrix, thereby reducing the insulation performance.

[0149] Example 1 and Comparative Examples 9-12 explore the effect of the selection of activators on the performance of solder paste. In Comparative Example 9, the activator contains only succinic acid. Since succinic acid is active at 180-230°C and decomposes at temperatures exceeding 230°C, the residual amount of solder paste after soldering in Comparative Example 9 is lower than that in Example 1. However, since there is no active component at temperatures exceeding 230°C, the fatigue resistance of the solder paste is significantly reduced, and the void rate is also significantly increased. The activator of Comparative Example 10 contains only adipic acid, and its active temperature range is 230-260°C, and its wettability and fatigue resistance are significantly reduced. This shows that the present invention selects succinic acid and adipic acid as activators, and the active temperatures of the two are different. Succinic acid is active at 180-230°C and decomposes at temperatures exceeding 230°C, so there is no residue after soldering, while adipic acid is active at 230-260°C, just in the soldering area, which can effectively reduce solder voids. By comparing Example 1 and Comparative Examples 11-12, it can be seen that when the activator is succinic acid and adipic acid in a mass ratio of 1:(1.5-3), the solder paste can have good wettability and fatigue resistance and can reduce the void rate.

[0150] In summary, the solder paste of the present invention has the advantages of good soldering strength, fatigue resistance, low voids and high insulation resistance.

[0151] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A fatigue-resistant and highly reliable solder paste, characterized in that: Made of the following raw materials in mass percentage: 85-90% alloy solder powder and 10-15% paste flux, wherein the alloy solder powder includes main solder powder, alloy powder A and alloy powder B, the main solder powder includes Sn, Ag, Cu and Sb, the alloy powder A includes Bi and / or In, and the alloy powder B includes at least one of Co, Ni, Ti, Nb, Cr, Mo and B; The paste flux comprises the following raw materials in parts by weight: 5-10 parts of an activator, 1-5 parts of a rheological agent, 20-30 parts of an organic solvent, 20-30 parts of a paste-forming agent, 0.1-0.5 parts of a modified filler and 0.1-0.5 parts of a corrosion inhibitor; the activator comprises succinic acid and adipic acid in a mass ratio of 1:(1.5-3); the rheological agent is a polyamide rheological agent; the organic solvent is a composition of a low boiling point solvent and a high boiling point solvent in a mass ratio of (1-2):1, the low boiling point solvent comprises dipropylene glycol methyl ether and / or ethylene glycol monobutyl ether, the high boiling point solvent comprises at least one of tripropylene glycol butyl ether, diethylene glycol butyl ether, hexanediol, 2-ethyl-1,3 hexanediol and pentanediol; the paste-forming agent is polyethylene glycol; The preparation method of the modified filler comprises the following steps: S1. Mix nickel powder, aluminum oxide and a co-solvent, stir evenly, and obtain a precursor dispersion liquid, wherein the co-solvent is a mixed solvent of ethanol, hydrochloric acid and acetic acid, and the mass ratio of the co-solvent, the nickel powder and the aluminum oxide is (5-6):1:(1.5-3); S2, adding polyvinyl pyrrolidone to the precursor dispersion, stirring evenly, to obtain a precursor dispersion, wherein the mass ratio of polyvinyl pyrrolidone to the precursor dispersion is (0.1-0.2):1; S3, electrospinning the precursor dispersion to obtain composite fiber paper, drying the composite fiber paper, and sintering the composite fiber paper in an oxygen-free environment at 1000-1500° C.; S4. Soaking the sintered composite fiber paper in an epoxy resin mixture for curing, taking it out and crushing it to obtain the modified filler, wherein the epoxy resin mixture includes epoxy resin, curing agent and catalyst in a mass ratio of 1:1:(0.01-0.03), and the mass ratio of epoxy resin to sintered composite fiber paper is (2-3):

1.

2. The fatigue-resistant and highly reliable solder paste according to claim 1, characterized in that: The alloy welding powder is composed of the following components in percentage by mass: Ag 0.1-5.0%, Cu 0.1-1.0%, Sb 1-6%, In 1-5%, Bi 1-5%, Co0.005-0.1%, Ni 0.05-0.1%, Ti 0.001-0.5%, Nb 0.001-0.3%, Cr0.005-0.1%, Mo0.005-0.2%, B 0.001-0.01%, and the balance is Sn and unavoidable impurities.

3. The fatigue-resistant and highly reliable solder paste according to claim 1, characterized in that: The corrosion inhibitor is triazole and / or benzotriazole.

4. The fatigue-resistant and highly reliable solder paste according to claim 1, characterized in that: The low boiling point solvent is a composition of dipropylene glycol methyl ether and ethylene glycol monobutyl ether in a mass ratio of 1: (0.5-0.7), and the high boiling point solvent is a composition of tripropylene glycol butyl ether and diethylene glycol butyl ether in a mass ratio of 1: (0.8-1).

5. The fatigue-resistant and highly reliable solder paste according to claim 1, characterized in that: The volume ratio of ethanol, hydrochloric acid and acetic acid in the co-solvent is (9-11):1:

1.

6. The fatigue-resistant and highly reliable solder paste according to claim 1, characterized in that: The curing agent is hexahydrophthalic anhydride, and the catalyst is imidazole.

7. The fatigue-resistant and highly reliable solder paste according to claim 1, characterized in that: In the preparation step S3 of the modified filler, the drying temperature is 70-80° C., the time is 10-14 hours, and the sintering time is 1-2 hours.

8. The fatigue-resistant and highly reliable solder paste according to claim 1, characterized in that: In the preparation step S4 of the modified filler, the curing is a three-stage curing, the first stage curing temperature is 65-75°C, the time is 1-2h, the second stage curing temperature is 100-120°C, the time is 1-2h, and the third stage curing temperature is 140-160°C, the time is 3-4h.

9. The method for preparing the fatigue-resistant and highly reliable solder paste according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) heating and stirring an activator, a rheological agent, an organic solvent, a paste-forming agent and a corrosion inhibitor until the mixture is uniformly mixed, and then adding a modified filler after heating to 70-80° C. and stirring to obtain the paste flux; (2) After the temperature of the paste flux drops to 25±3° C., gradually add alloy solder powder to the paste flux and stir evenly to obtain the fatigue-resistant and highly reliable solder paste.

Citation Information

Patent Citations

  • ski binding with a lever tensioner in front of the toe cheeks for tightening the heel strap

    DE432539C

  • Low-rosin halogen and lead-free solder paste and preparation method thereof

    CN102554489A

  • Soldering flux for high-performance Sn-Bi system low-temperature lead-free soldering paste and preparation method of soldering flux

    CN117399846A

  • High-activity tin-bismuth-silver series lead-free solder paste with low residue after welding and preparation method thereof

    CN117644315A

  • Flux composition for solder, solder paste, and method of soldering

    US20040250919A1